2016
DOI: 10.7860/jcdr/2016/17111.7364
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Study on Serum Lactate Dehydrogenase (LDH)-Prognostic Biomarker in Carcinoma Breast

Abstract: Serum LDH monitoring can be used as a prognostic biomarker in patients of breast cancer. For confirmation of this finding, we require further more studies on larger sample size and long-term follow-up in patients specifically with higher serum LDH levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 14 publications
4
15
0
Order By: Relevance
“…Thus, high levels of serum LDH in such kind of patients may be considered as an early warning sign of recurrence or metastasis. 27 In present study, both MTV and TLG levels were found to be positively correlated with serum LDH in all cancer types (for MTV: rho= 00.417, p< 0.05; for TLG: rho= 0.365, p< 0.05).…”
Section: Discussionsupporting
confidence: 58%
“…Thus, high levels of serum LDH in such kind of patients may be considered as an early warning sign of recurrence or metastasis. 27 In present study, both MTV and TLG levels were found to be positively correlated with serum LDH in all cancer types (for MTV: rho= 00.417, p< 0.05; for TLG: rho= 0.365, p< 0.05).…”
Section: Discussionsupporting
confidence: 58%
“…These conditions (high consumption of glucose and hypoxic environment) lead to higher LDH levels. More generally, a high LDH level is known to be a factor of poor prognosis in other cancers, such as lung15 and breast cancer16, and two other studies in NEC (pulmonary17 and colorectal12) also reported high LDH serum levels. Among 61 patients with available AST data at diagnosis, 31% had AST ≥ 2 ULN and they were associated with poorer outcome in multivariate analysis.…”
Section: Discussionmentioning
confidence: 87%
“…Six parameters related to body size were determined: body weight/height/length, bust, chest depth, neck size, and two other traits, such as wool length, and shear amount (defined as the weight of the fleece post shearing) 17 ; Thirteen physiological parameters: body temperature (Temperature), breathe rates (Breathe), pulse rates (Pulse), pulse interval (pulse interval), red-cell numbers (RBC), hematocrit, HCT, erythrocyte mean corpuscular volume (MCV) 17 , mean corpuscular hemoglobin (MCH), Mean corpuscular hemoglobin concentration (MCHC) 18 , Hemoglobin (HGB), Platelet (PLT), Red blood cell volume distribution width coefficient variation (RGW-CV), White blood cell count (WBC). Biochemical parameters: Glutamic pyruvic transaminase (ALT) 19 , Glutamic oxalacetic transaminase (AST) 19 , Total protein (TP), Albumin (ALB), Globulin (GLO), Alkaline phosphatase (ALP), Lactate dehydrogenase (LDH), Cholinesterase (PCHE) 20 , Glucose (GLU), Total cholesterol (CHOL) 21 , Total calcium (CA); Nine blood-gas parameters: blood pH, pressure CO 2 (pCO 2 ), O 2 saturation (O 2 S), concentration of HCO 3 - , standard bicarbonate, total CO 2 concentration, Base excess (BE), Standard base excess (SBE); structural parameters related to Lung tissue: bronchial, thin bronchial, end thin bronchial, alveolar numbers per area (A N /m 2 ), thick alveolar interval (TAI).…”
Section: Methodsmentioning
confidence: 99%